Reconstrucción paleoflorística a partir de los conjuntos palinológicos recuperados de los lacustres Villa Alegría y Cerro Prieto en el Valle de Tehuacán-Cuicatlán, Puebla y Oaxaca - Rosales Torres, Sara (Universidad Autónoma Metropolitana, 2016)
The main objective of this research was to reconstruct the paleoflora of Lacustrine Villa Alegr ia (named by Dávalos -Álvarez, 2006) and the Cerro Prieto travertine through paleopal ynologi cal analysis, in addition to establish ing palynofloristic affinities with other Neogene and Paleogene formations found in Mexico. The study area includes two localit ies situated within the Tehuacan -Cuicatla n Valley: Lacustrine Villa Alegria to the north of the valley in Puebla State, a nd the Cerro Prieto travertine in the south of the valley, Oaxaca State. In Lacustrine Villa Alegria, three sections were prospected and a total of 45 travertine rock samples were collected. In the Cerro Prieto travertine, five sections w ere prospected and a total of sixty samples were collected. All samples were processed under the conventional method of extracting fossil pollen (Traverse, 2007). In Lacustrine Villa Alegria, 44 samples contained a total of 18,389 palynomorphs was counted, of which 2,240 pertain to pollen and spores, while the rest were algae and fungal spores. 68 taxa were identified, of which 80% (n = 55) match angiosperms, 5.9% (n = 4) match gymnosperms and 14.7% (n = 10) are spores. In the Cerro Prieto travertine, of the 60 processed samples 58 were positive. Sums of 14,935 palynomorphs were counted there, of which 2546 pertain to pollen and spores and 12,412 are algae and fungal spores. 53 taxa were identified, of which 71.7% (n = 38) match angiosperms, 7.5% (n = 4) are gymnosperms and 20.7% (n = 11) pertain to spores.The paleo palynological assemblages recovered from both locations were plotted with the Tilia Graph (Grimm, 1997) program. They were analyzed using the CONISS method in order to determine pal ynozone s. In s ection s VA -2 and VA- 3 of Lacustrine Villa Alegr ia, the most abundant floristic element was Fraxinus sp., followed by Alnus sp. and Asteraceae. In s ection VA- 1 the dominant element was Bursera sp., followed by Anacardiaceae. In most sections of the Cerro Prieto travertine, the genera that dominated palynological assemblages were Fraxinus sp, Quercus sp. and Pinus sp. Bursera sp. was dominant in s ection CP -3 of said locality. Two palynozones were defined in al l Lacustrine Villa Alegria and Cerro Prieto travertine sections; they were characterized by different taxa, and the greatest diversity of species was found to be concentrated mid-section. Richness (S), diversity (H ') and evenness (J') of the taxa recovered within the palynological assemblages were analyzed. In Lacustrine Villa Alegria, the highe st level of richness was obtained in section VA- 3 with S = 2 and the highest Shannon Wiener diversity rate was obtained in section VA- 2 with H'= 2.95, as well as the highest value of the Pielou evenness index with J '= 0.77. For the Cerro Prieto travertine, the highest richness value was obtain ed from section 3 with S = 38, the highest diversity was also found in section 3 with H'= 3.36, and the highest evenness value was observed in sections CP -3 and CP -4, both with J' = 0.75. B ased on actualism, the taxa identified within thepaleo palynological assemblages recovered from Lacustrine Villa Alegria and the Cerro Prieto travertine were classified and assigned to potential vegetation types that were part of the local and regional flora, which grew accordingly along an altitudinal gradient. Multivariate statistical cluster analysis and principal components (PC) were calculated to corroborate floristic interpretation. The cluster analysis for Lacustrine Villa Alegria grouped the observed floristic elements in to five probable types of vegetation: cloud forest, pine -oak forest, gallery forest, deciduous tropical forest and desert scrub. On the other hand, cluster analysis grouped the observed floristic elements in to four likely types of vegetation for the Cerro Prieto travertine: cloud forest, pine -oak forest, tropical deciduous forest and desert scrub. P rincipal component analysis in both locations corroborated the results obtained through cluster analysis. Based on floristic interpretation and statistical analysis, possible paleovegetation was rebuilt. For Lacustrine Villa Alegría, inferred vegetation types were cloud forest, pine -oak forest, gallery forest, deciduous tropical forest and desert scrub, which grew according to an altitudinal gradient of moisture. C loud forest occupied the surrounding areas with the greatest altitude and highe st humidity, followed by the pine -oak forest; meanwhile, tropical deciduous forest grew at the bottom of the Tehuaca n- Cuicatla n Valley and desert scrub was established in the drier areas. Veget ation types that may have existed at the time of deposition the Cerro Prieto travertine are: cloud forest, pine- oak tropical deciduous forest and desert scrub. R egional flora was represented by cloud forest, pine -oak forest and gallery forest, while tropic al deciduous forest and possible desert scrub represented local flora.The lakeside town Villa Alegr ia showed greater floristic affinity with the Tehuac an formation than the Cerro Prieto travertine . Likewise, there is a close paleo phytogeographi c relations hip between both Lacustrine Villa Alegria and the Cerro Prieto travertine and other for mations in the Tehuacan -Cuicatla n Valley and central Mexico. Paleo phy togeographic correlation separated central Mexican basins from those in the south; two distinct groups derived from floristic differences. Through stratigraphic correlatio n, the age set by Dávalos -Álvarez (2006) for Lacustrine Villa Alegria was P liocene- Pleistocene while the Cerro Prieto travertine was Pliocene; paleopal ynological analys is did not change that . C orrelation was discovered between the abundance biozones of both sites: the middle of section VA- 3 of Lacustrine Villa Alegria and sections CP -1 and CP -2 of the Cerro Prieto travertine. Keywords: paleofloristic reconstruction, Tehuacan -Cuicatla n, travertine, cloud forest, pine -oak forest, tropical deciduous forest, desert scrub.; El objetivo fundamental de la presente investigación fue reconstruir la paleoflora de los lacustres Villa Alegría y los travertinos Cerro Prieto mediante análisis paleopalinológicos y establecer sus afinidades paleofitogeográficas con otras formaciones Neógenas y Paleógenas de México. El área de estudio comprende dos localidades ubicadas en el Valle de Tehuacán - Cuicatlán: los lacustre s Villa Alegría al norte del valle en el estado de Puebla y los travertinos Cerro Prieto al sur del valle en el estado de Oaxaca. En los lacustres Villa Alegría se prospectaron tres secciones y se colectaron un total de 45 muestras de roca travertino. En los travertinos de Cerro Prieto, se prospectaron cinco secciones y se colectaron un total de 60 muestras. L as muestras se procesaron por el método convencional de extracción de polen fósil (Traverse, 2007). En Villa Alegría 44 de 45 muestras presentaron un total de 18,389 palinomorfos, de los cuales 2, 240 correspondieron a polen y esporas, el resto a algas y fungosporas. Se identificaron 68 taxa de los cuales el 80% (n=55) correspondieron a angiospermas, el 5.9% (n=4) a gimnospermas y el 14.7 % (n= 10) a esporas. En Cerro Prieto de las 60 muestras procesadas 58 fueron positivas. En esta localidad se contabilizaron un total de 14,935 palinomorfos, de los cuales 2,546 correspondieron a polen y esporas, 12,412 de algas y fungosporas. Se identificaron 53 taxa de los cuales 71.7% (n=38) corresponden a angiospermas, el 7.5% (n= 4) a gimnospermas y el 20.7% (n=11) corresponde a esporas. Los conjuntos paleo palinológicos recuperados de ambo s lacustres se analizaron con el fin de determinar las palinozonas. En la sección VA- 2 y VA -3 de los lacustres Villa Alegría el elemento florístico más abundante fue Fraxinus sp . , seguido por Alnus sp. y la familia Asteraceae. En la sección CP -1 el elemento dominante fue Bursera sp., seguido por la familia Anacardiaceae. En la mayoría de las secciones de Cerro Prieto los géneros que dominaron los conjuntos paleo palinológicos fueron Fraxinus sp, Pinus sp . y Quercus sp . . En la sección CP -3 de esta localidad domino Bursera sp . . En las ocho secciones de los lacustres Villa Alegría y de los travertinos Cerro Prieto, quedaron definidas dos palinozonas que se caracterizaron por diversos taxa y se observó que la mayor diversidad de especies se concentró fundamentalmente en la parte media de la columna estratigráfica. Se analizó la riqueza (S), diversidad (H’) y la equitatividad (J’) de los taxa recuperados en los conjuntos paleo palinológicos. Para los lacustres Villa Alegría se observó que la mayor riqueza se presentó en las ección VA -3 con S=29, el mayor índice de diversidad de Shannon Wiener lo obtuvo la sección VA- 2 con H’= 2.95, el valor más alto del índice de equitatividad de Pielou con J’=0.77 lo obtuvo la misma sección. Para los travertinos Cerro Prieto el valor más alto de riqueza se observó en la sección CP -3 con S =38, la diversidad más alta la presentó la sección CP -3 con H’= 3.36 y el valor más alto de equitatividad se observó en las secciones 3 y 4, ambas con J’= 0.75. Los taxa identificados en los conjuntos paleo palinológicos recuperados de los lacustres Villa Alegría y los t ravertinos C erro Prieto fueron asignados con base en el actualismo a los probables tipos de vegetación que formaron parte de una flora local y regional, la cual se distribuía a lo largo de un gradiente altitudinal. Se realizaron análisis estadísticos multivariados, de conglomerados (clúster) y de componente s principales (PC) para corroborar las interpretaciones florísticas. Con base en la interpretación florística y los análisis estadísticos se reconstruyó la posible paleovegetación . Los análisis de agrupamiento para los lacustres Villa Alegría y los travertinos Cerro Prieto, agruparon a los elementos florísticos en cinco probables tipos de vegetación: bosque mesófilo de montaña, bosque de pino-encino, bosque de galería, bosque tropical caducifolio y matorral xerófilo. Los análisis de componentes principales en ambas localidades corroboraron los resultados obtenidos para los análisis de agrupamiento. Esta vegetación se distribuía en un gradiente altitudinal de humedad en donde el bosque mesófilo de montaña ocupaba las zonas aledañas más altas y con mayor humedad, seguido por el bosque de pino- encino, en tanto que en el fondo del Valle de Tehuacán- Cuicatlán se estableció el bosque tropical caducifolio y en las partes más secas el matorral xerófilo. La flora regional estuvo representada por el bosque mesófilo y el bosque de pino- encino en tanto que la flora local quedo representada por el bosque tropical caducifolio y un probable matorral xerófilo.Los lacustres Villa Alegría presentan una mayor afinidad florística con la Formación Tehuacán que con los travertinos Cerro Prieto. Así mismo, se observó una estrecha r elación paleofitogeográfica de estos la custres con otras formaciones presentes dentro del Valle de Tehuacán -Cuicatlán y en el cen tro del país. La correlación paleofitogeográfica separó a las cuencas del centro de las del sur del país en do s grupos bien definidos de acuerdo a sus diferencias florísticas La edad establecida por Dávalos -Álvarez (2006) por correlación estratigráfica para los lacustres Villa -Alegría fue Plioceno -Pleistoceno y para los travertinos Cerro Prieto fue Plioceno; esta edad n o se modificó con los análisis paleopalinológicos en este estudio . Se realizó una correlación bioestratigráfica entre los lacustres Villa Alegría y los travertinos Cerro Prieto basada en las biozonas de abundancia del género Fraxinus sp. y se observó que hay una correlación por biozonas de abundancia entre la parte media de la sección VA -3 de los lacustres Villa Alegría y las secciones CP -1 y CP -2 de los travertinos Cerro Prieto. Palabras clave: reconstrucción palinoflorística, Tehuacán -Cuicatlán, travertinos, bosque mesófilo de montaña, bosque de pino encino, bosque tropical caducifolio, matorral xerófilo.